The influence of media exposure on voters behavior during the sumbawa 2020 local election (PILKADA) - Sarina Yusup (Tanjung Malim, 2023)
The influence of media exposure on voters behavior during the sumbawa 2020 local election (PILKADA) by Sarina Yusup